Stimulatory effect of eucalyptus essential oil on the germination and early growth of Eucalyptus grandis seedlings - Steffen, Ricardo Bemfica (2010)
The use of essential oil and extracts from plants is becoming an efficient alternative in the biostimulation on growth and protection of plants. The aim of this work was to evaluate the use of leaf essential oil of Eucalyptus grandis on the germination and the  development of Eucalyptus grandis seedlings in nursery conditions. The eucalyptus seeds were exposed to the concentrations of 0, 10, 25, 50, 75 and 100 Î¼L L-1 of the essential oil in controlled conditions. The eucalyptus seedlings were sprayed with 0, 20, 30, 40, 50 and 60 Î¼L L-1 of the essential oil per plant, at intervals of seven days. The effect of this application on the seedling development were analyzed after 30 and 60 days. The results show that the germination was significantly higher when the seeds were exposed to 25 Î¼L L-1 of the essential oil. The application of essential oil in the concentration of 30 and 40 Î¼L L-1 provided higher growth of the aerial part and of the roots in greenhouse conditions, being an effective alternative to biostimulation the vegetative growth of eucalyptus seedlings.